PENGARUH KOMPENSASI, MOTIVASI, DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN - Putra Wibawa, I Gede; sriathi, A.A.Ayu (E-Jurnal Manajemen, 2017)
Company in running its operations as possible improve employee performance. The purpose of this study to determine effect of compensation, motivation and work discipline on employee performance Blue Marlin Café Kedonganan. This research conducted census method and sample used 67 respondents, by multiple linear regression. The results show that compensation has a significant positive effect on employee performance Blue Marlin Café Kedonganan. Motivation has a significant positive effect on employee performance of Blue Marlin Café Kedonganan. Work discipline has a significant positive effect on employee performance of Blue Marlin Café Kedonganan. Advice can be given, Blue Marlin Café Kedonganan must pay attention to the compensation with a fair policy in accordance with the achievement of employees in improving their work performance. The management is expected to maintain and pay attention to the motivation given to subordinates when having difficulty in completing their work. Keywords: compensation, motivation, work discipline, employee performance